2022
DOI: 10.1186/s12874-022-01630-9
|View full text |Cite
|
Sign up to set email alerts
|

Multi-dimensional vulnerability analysis on catastrophic health expenditure among middle-aged and older adults with chronic diseases in China

Abstract: Objective Middle-aged and older adults are more likely to suffer from chronic diseases because of their particular health characteristics, which lead to a high incidence of catastrophic health expenditure (CHE). This study plans to analyse the different factors affecting CHE in middle-aged and older adults with chronic diseases, target the vulnerable characteristics, and suggest groups that medical insurance policies should pay more attention to. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…For instance, type of illness. Studies from China, Bangladesh, Malaysia, and Kenya showed that patients having chronic disease, NCD and cancer face higher CHE [ 25 , 26 , 31 , 32 , 41 , 48 , 49 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, type of illness. Studies from China, Bangladesh, Malaysia, and Kenya showed that patients having chronic disease, NCD and cancer face higher CHE [ 25 , 26 , 31 , 32 , 41 , 48 , 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…Again, accessed care is another influential predictor of CHE. Studies from Iran, China, and Vietnam concluded that those who are taking inpatient care very likely face CHE [ 4 , 36 , 47 , 48 , 54 ]. Moreover, diseases for which the treatment cost is higher have higher CHE.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With the increased aging in the global population, comorbidities in older adults will become a common problem [19] that societies of all countries will face. Therefore, strategies to reduce the disease burden of older patients with comorbidities have become the focus of the governments, scienti c community, and industry [20]. The input-output research of chronic disease health management in China indicated that the input-output ratio of disease prevention is 1:11.72 [21]; especially, disease prevention can not only effectively reduce the burden of disease, but also signi cantly improve the quality of life of patients [22].…”
Section: Discussionmentioning
confidence: 99%
“…Among them, the number of PCIs (ρ31), the number of beds (ρ32), and the number of personnel (ρ33) characterized the capabilities of PCIs. Physical characteristics are fundamental factors that promote the use of medical resources [ 50 , 51 ], while chronic diseases and activities of daily living (ADL) are often proxy variables [ 52 , 53 ]. For hypertension, patients tend to choose PCIs [ 54 ].…”
Section: Methodsmentioning
confidence: 99%